2005
DOI: 10.1186/1471-2407-5-45
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gene expression in prostate cancer, normal appearing prostate tissue adjacent to cancer and prostate tissue from cancer free organ donors

Abstract: Background: Typical high throughput microarrays experiments compare gene expression across two specimen classes -an experimental class and baseline (or comparison) class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 31 publications
(29 reference statements)
6
104
0
1
Order By: Relevance
“…This revealed a slightly lower expression of endogenous SIM2s in the human prostate carcinoma DU145 cells compared with other prostate and pancreatic carcinoma cell lines (Figure 1a). Consequently, independently derived polyclonal cell pools showing stable ectopic expression of carboxy-terminal myc-tagged human SIM2s (SIM2s.myc) were generated in DU145 cell line to emulate an aberrant increase in SIM2s in prostate cancers compared with benign samples, as previously observed from several studies by others (Su et al, 2002;Chandran et al, 2005;Halvorsen et al, 2007). Puromycin-resistant control (Control) pools were generated by incorporation of the empty expression vector.…”
Section: Identification Of Bnip3 As a Putative Target Of Repression Bmentioning
confidence: 93%
See 1 more Smart Citation
“…This revealed a slightly lower expression of endogenous SIM2s in the human prostate carcinoma DU145 cells compared with other prostate and pancreatic carcinoma cell lines (Figure 1a). Consequently, independently derived polyclonal cell pools showing stable ectopic expression of carboxy-terminal myc-tagged human SIM2s (SIM2s.myc) were generated in DU145 cell line to emulate an aberrant increase in SIM2s in prostate cancers compared with benign samples, as previously observed from several studies by others (Su et al, 2002;Chandran et al, 2005;Halvorsen et al, 2007). Puromycin-resistant control (Control) pools were generated by incorporation of the empty expression vector.…”
Section: Identification Of Bnip3 As a Putative Target Of Repression Bmentioning
confidence: 93%
“…Although the focus has mainly been on SIM2s in these tumour types, SIM2l messenger RNA (mRNA) has also been found to be expressed in tumours and tumour-derived cell lines of the pancreas (DeYoung et al, 2003b) and in prostate tumours (Halvorsen et al, 2007), but not in the corresponding normal cell lines or benign tissue samples. Several independent microarray studies have found SIM2 to be the second most consistently up-regulated gene in prostate tumours, while not being expressed in the corresponding benign tissue (Su et al, 2002;Chandran et al, 2005;Halvorsen et al, 2007). SIM2 over-expression in human pancreatic carcinoma samples and derived cell lines compared with normal ductal epithelium controls has also recently been found in the most comprehensive genome-wide analysis to date (Jones et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Between the two datasets, there are a total of 113 tumor samples and 113 normal samples [15,16]. Normal samples are extracted from tissue adjacent to prostate tumors.…”
Section: Microarray Datamentioning
confidence: 99%
“…Field cancerization is however evident at the genetic as well as the epigenetic level, as we have shown by altered telomeres in whole tissue TAHN extracts (11) and as shown by others by gene promoter methylation of APC, RARß2 and RASSF1A (34). Field cancerization in prostatic tissues is also evidenced by RNA/ protein expression analysis (35,36). In a similar study, but without validation by qRT-PCR, Chandran and colleagues reported differentially expressed transcripts when comparing tumor associated matched tissues to cancer-free controls utilizing an Affymetrix platform (35).…”
Section: Discussionmentioning
confidence: 84%
“…Field cancerization in prostatic tissues is also evidenced by RNA/ protein expression analysis (35,36). In a similar study, but without validation by qRT-PCR, Chandran and colleagues reported differentially expressed transcripts when comparing tumor associated matched tissues to cancer-free controls utilizing an Affymetrix platform (35). Of note, the authors claim that these transcripts would not be identified as differentially expressed when compared to tumors.…”
Section: Discussionmentioning
confidence: 95%